Microfinance : handbook (Philippines) - Favis-Villafuerte, Nelly (Makati City, Philippines : Apples of Gold, 2007)
This handbook is primarily for the general public - including but not limited to microfinance practitioners (like NGOs, rural banks, thrift banks, credit cooperatives, cooperative banks); microfinance policymakers and regulators, businessmen, lawyers etc.
Includes index.
osa02/05/13
Loans
Keywords: Microfinance; Microfinance - Philippines